You first need to cross multiply to get 8x+8=6x^2-6. Then make the function into 6x^2-8x-14=0 which can be simplified into 3x^2-4x-7=0 by dividing the equation by 2. Then you must split the middle(-4x) to get 3x^2+3x-7x-7=0. This simplifies to 3x(x+1)-7(x+1)=0 and then to (3x-7)(x+1)=0. From here you just solve for each root which you will find are x= -1 and 7/3
Answer:
i actually dont know
Step-by-step explanation:
Answer:
.0006
Step-by-step explanation:
I'm not sure if this is correct.. sorry if this is wrong.. :(
The probability of an event cannot be less than 0 because 0 means it's impossible. The probability of an event cannot be more than 1 because 1 means that it's certain that it will happen. That's why the probability must be between 0 and 1.